IN VITRO ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF PHOENIX PUSILLA ROOT EXTRACT - S, Vijaya Bharathi; V, Anuradha; G, Rubalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to analyze the bioactive compound presence, in vitro antioxidant and antimicrobial potential of Phoenix pusilla root extract. Methods: Extracts were prepared with ethanol, acetone, and hexane by Soxhlet method. Then, the extracts were checked for phytochemicals presence or absence. In vitro antioxidant activity was analyzed by checking its scavenging ability and reducing property. Antibacterial was assayed by well diffusion method and antifungal activity using sabouraud dextrose broth. Results: The results showed that the ethanolic root extract contains alkaloids, flavonoids, saponin, tannin, and triterpenoids have potent antioxidant activity and inhibitory activity against certain Gram-positive, Gram-negative, and fungi. Conclusion: The present study revealed the significance of the plant as a drug. Further, in vivo study is needed to be used as curative agent for different health illness.